THE POTENTIAL OF THE SCHOOL LIBRARY TO PROMOTE’STUDENTS’ SELF-DIRECTED LEARNING - Laškova, Agnese; Ročāne, Maija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Motivating students to read more is becoming increasingly important nowadays. The ability to understand the meaning of a text, to analyse, critically evaluate and verify the information and facts, as well as formulate one's own opinion - this is a skill that is vital for modern people living in the 21st century - the century of fake news. The latest PISA 2022 study shows that average reading performance in Latvia has fallen in comparison to 2018 results. The average reading achievement of pupils of Latvia has been falling every year since 2012. The challenge for schools is to use their internal resources to stimulate pupils' interest in reading in order to break this trend. One of the school's internal resources is a library. The school library has an important role to play in motivating pupils to read and to learn. It is an environment that encourages and supports reading and self-directed learning. The aim of this publication is to describe possibilities of raising reading interest and self-directed learning opportunities in school library.